Lymphatic Reconstruction in Kidney Allograft Aggravates Chronic Rejection by Promoting Alloantigen Presentation - Jinwen Lin; Ying Chen; Huijuan Zhu; Kai Cheng; Huiping Wang; Xianping Yu; Mengmeng Tang; Jianghua Chen (Frontiers in Immunology, 2021)
Chronic rejection of the renal allograft remains a major cause of graft loss. Here, we demonstrated that the remodeling of lymphatic vessels (LVs) after their broken during transplantation contributes to the antigen presenting and lymph nodes activating. Our studies observed a rebuilt of interrupted lymph draining one week after mouse kidney transplantation, involving preexisting lymphatic endothelial cells (LECs) from both the donor and recipient. These expanding LVs also release C-C chemokine ligand 21 (CCL21) and recruit CCR7+ cells, mainly dendritic cells (DCs), toward lymph nodes and spleen, evoking the adaptive response. This rejection could be relieved by LYVE-1 specific LVs knockout or CCR7 migration inhibition in mouse model. Moreover, in retrospective analysis, posttransplant patients exhibiting higher area density of LVs presented with lower eGFR, severe serum creatinine and proteinuria, and greater interstitial fibrosis. These results reveal a rebuilt pathway for alloantigen trafficking and lymphocytes activation, providing strategies to alleviate chronic transplantation rejection.